Adoption of energy management system in industrial sector of Azerbaijan - Pashayeva, Matanat (ADA University, 2019)
Azerbaijan, a country rich with oil and gas resources has set a target to increase the contribution of non-oil sectors in the economy to ensure sustainable development in the country. To this end, dedicated strategic roadmaps for the development of individual sectors of the economy with due identification of measures were developed by GoA. Energy efficiency measures across the sectors of the economy were established as one of the top priority to reach resource savings. To this end, the researcher has set a target to explore adoption of energy management systems in the industrial sector of Azerbaijan as a solution to reach mass scale energy efficiency across subsectors of the industry. Existing conditions, barriers and expectations of key stakeholders for adoption of EnMS were defined through the analysis of primary data. It was found out that there is presently very low interest to energy management systems which seems natural where the energy prices are cheap and easily accessible and with no relevant regulation applicable. Considering all the mentioned factors, government intervention is seen as necessary for regulating, incentivizing and supporting the market to reaching expected targets. Adoption of energy management system within this study is considered in demand side of industrial sectors of Azerbaijan. The researcher has studied policy pathway of the European countries where the significant improvement has been achieved on mass voluntary adoption of energy management systems not only across the energy intensive sectors but also small and medium size enterprises. Studies shows positive correlation among the existence of energy management program and commitment of incumbent organizations to energy efficiency. Moreover, there is positive correlation between design and characteristics of policy (ADEME, Energy Efficiency Policies in EU). But the level of yielded commitment varies across countries and is not positively correlated with only high impact measures, due to various need to stimulate separate drivers across countries (ADEME, Energy Efficiency Policies in EU). It was also found out that mandatory policy packages generate commitments but only voluntary agreements enhance high commitment. The role of competent energy managers in the adoption of energy management systems by the industrial organizations should be emphasized as well. The required skills for energy managers are not only technical, but also managerial. Moreover, primary data derived through the interviews and survey were analyzed within this study and found out energy management is either partially being implemented by the local enterprises or not implemented. Energy management system is new management system in the country and could be attractive for the local organizations for adoption if only they receive relevant support and incentives. Low interest to energy management systems by the industrial enterprises is associated with cheap energy prices, lack of relevant regulation in the country. Referring primary and secondary data and considering efforts taken by the Government of Azerbaijan so far and their main challenges in this road in terms of adopting energy management programs, the researcher has proposed policy packages including prescriptive, economic and information components as per the expectations of the target audience and giving them option to select one. The proposed policy packages are designed for both large industrial organizations and small and medium size organizations. Here, the will of the Government and incumbents is reflected in one package which will yield high commitments and high contribution of industrial incumbents, and accordingly generate win-win scenario. Moreover, energy consumption trend, growth rate were reviewed and underlying reasons for fluctuations were explained during 2008-2017 years. Accordingly, the activity based value added of industrial subsectors, as well as energy intensity of the industrial subsectors were reviewed by the researcher. It was found out that mining sector of Azerbaijan is the most energy efficient sector which includes the amount of oil and gas production as well. But the basic metal subsector of industry is the most energy intensive sector among the concerned industries within this study. Change factor analysis was made to find out underlying reason for change in final energy consumption during the period of 2008-2017 and found out that activity effect was the key reason of change in energy demand. Energy efficiency indicator of industrial subsectors were compared with the developed countries relevant indicators and found out the there is significant energy saving opportunity in chemical and petrochemical industry of Azerbaijan. Based on this finding the researcher proposes adoption of energy management systems in chemical and petrochemical industry of Azerbaijan. The findings from the analysis were used to formulate relevant policy recommendations for facilitating adoption of energy management systems in industrial sub sectors of Azerbaijan.
Keywords: Business; Energy management.; Energy management -- Azerbaijan.; Petroleum industry and trade -- Political aspects -- Azerbaijan.; Petroleum -- Transportation -- Azerbaijan.; Pipelines -- Azerbaijan.